x2 + y2 - 2x + 4y + 2 = 0

x2 + y2 - x + y + 3 = 0

x2 + y2 - 2x + 4y - 4 = 0

x2 + y2 - x + y + 2 = 0

Answers (1)

Know the Answer?

Not Sure About the Answer?

Find an answer to your question ✅ *“Determine the general form of the equation for the circle (x - 1) 2 + (y + 2) 2 = 3. x2 + y2 - 2x + 4y + 2 = 0 x2 + y2 - x + y + 3 = 0 x2 + ...”* in 📘 Mathematics if you're in doubt about the correctness of the answers or there's no answer, then try to use the smart search and find answers to the similar questions.

Search for Other Answers
Newest Questions in Mathematics

A ski run is 1000 yards long with a vertical drop of 208 yards. Find the angle of depression from the top of the ski run to the bottom.

Answers (1)

Mali and Kai are growing sunflowers. Mail's sunflower measures 1 yard, 2 feet, 3 inches. Kai's sunflower measures 6 feet, 10 inches. What is the difference in height between Mail's and Kai's sunflowers?

Answers (1)

How does light travel after it leaves the light source?

Answers (1)

3 (a+7) = - 33 Step By Step Equation

Answers (1)

Which of the following equations is equal to 3x^2+27?

Answers (1)